Species diversification and phylogeographical patterns of birds in response to the uplift of the Qinghai-Tibet Plateau and Quaternary glaciations. Issue 2 (1st April 2014) - Lei, Fumin; Qu, Yanhua; Song, Gang
Abstract: The Qinghai-Tibet Plateau (QTP) is well known for being of great importance in the evolution of montane species due to its unique geological history and landform configuration, climate complexity, and diversified habitats. The effect of environmental changes since the Quaternary on species diversification, population genetic structure, and demography under environmental change can be studied using phylogenetic and phylogeographical approaches. Birds are the most well-studied group of all terrestrial vertebrates with regard to their response to climatic changes over time. Herein, we briefly review the species diversification of birds in response to the uplift of the QTP, focusing on summarizing the different phylogeographical patterns of birds on the Plateau, its southeastern margin, and the Eastern Himalayas and the reasons underlying these patterns. Speciation was found to be closely related to the uplift of the QTP, with different patterns of intraspecific processes: (1) no divergence within a single refuge was identified in a restricted semi-continuous area of the eastern margin of the Plateau; (2) two divergent lineages with separated refugia were located at the south-eastern and north-eastern margins of the plateau; and (3) multiple divergent lineages within subregions were found in the Eastern Himalayas. Glacial movements and induced climate change are considered to be key factors in shaping these different patterns. The species distributed mainly in the heavily ice-covered platform regions of the Plateau experienced population expansion following the retreat of the extensive glaciations, whereas the species distributed on the ice-free edges of the plateau maintained their population size at a stable level. Demographic stresses on the edge species might have been mitigated by the milder climate in comparison to their platform-distributed counterparts. Various behavioral and ecological characteristics, including dispersal capacity, habitat preference, and elevation specificity, along with evolutionary history might have helped to shape these different phylogeographical patterns.